Digital Ethics Education: Preventing Cyberbullying and Supporting Mental Health in Elementary Schools - Ulfa Dilah; Suci Rahmadhani (Yayasan Cerdas Pedia Indonesia, 2025)
This study addresses the escalating crisis of cyberbullying and its detrimental impact on the mental health of Indonesian elementary students in 2025. Utilizing a Systematic Literature Review (SLR) and bibliometric analysis of 73 core articles, the research examines how digital environments influence children’s moral reasoning through the theoretical lenses of Lawrence Kohlberg and Albert Bandura. Findings reveal that the